Percepção dos profissionais de saúde do CAPS AD sobre a Redução de Danos: história, nossas histórias, dias de luta, dias de glória - Dias, Claudia Oliveira (2018)
The current work’s object of detail was the perceptions from health professionals from a CAPS AD, at the Salvador municipality, about the practices adopted in the daily life at work, carried out for the care and follow up of alcohol and other drugs users, discussing those views from a human rights perspective. A qualitative and descriptive research was carried out, for the data collection 18 episodic interviews, recorded and transcripted, were done. At least one health professional of each category was included in the research, ranging from the ones carrying out assistencial actions, to the management, with the only criteria for inclusion being they had been assisting the drug users for at least one year. For the analysis, the Grounded Theory was utilized, because of its systemic and structured approach for the data analysis and category improvement, and because of its understanding about a coherence between the research issue and the selected information production technique. After a detailed analysis, 6 main categories appeared, divided in five blocs, each presenting six guiding directions: Treatment; First contact with the user and the AD clinic; RD meaning; RD actions at the job; Most lasting CAPS experience and most significant experience related to the job and when the approach becomes an issue. The study showed the team presented difficulties to work in a cohesive and harmonious manner, however it made clear that damage reduction is included in their daily routine and serves as a north when offering assistance to the drug users, respecting human rights. The research identified that the health care professionals perception is permeated by the rights to be different, to choice, to health and the right to be whoever one wishes.